Immediate impacts of COVID-19 pandemic on bean value chain in selected countries in sub-Saharan Africa - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Chirwa, Rowland; Templer, Noel; Rubyogo, Jean-Claude; Onyango, Patricia (Elsevier, 2021)
Africa's agriculture and food systems were already grappling with challenges such as climate change and weather variability, pests and disease, and regional conflicts. With rising new cases of COVID 19 propelling various African governments to enforce strict restrictions of varying degrees to curb the spread. Thus, the pandemic posed unprecedented shocks on agriculture and food supply chains in Sub Saharan Africa. In this study, we use survey data collected from nine countries in Central, Eastern, and Southern, Africa to understand the immediate impact of COVID-19 on production, distribution, and consumption of common beans, and possible food security implications. Descriptive analysis of data collected from bean farmers, aggregators, processors, bean regional coordinators, and mechanization dealers reveal that COVID-19 and government restrictions had impacted the availability and cost of farm inputs and labour, distribution, and consumption of beans in Eastern and Southern Africa. The immediate impacts were dire in Southern Africa with Central Africa slightly impacted. The production and distribution challenges negatively impacted on frequency and patterns of food consumption in households in Africa. Thus, the pandemic poses a greater risk to food security and poverty in the region. Governments could play a significant role in supporting the needs of smallholder farmers, traders and other actors through provision of subsidized agricultural inputs.